Moral Courage and Facing Others - Pianalto, Matthew (International journal of philosophical studies : IJPS, 2012)
Moral courage involves acting in the service of one's convictions, in spite of the risk of retaliation or punishment. I suggest that moral courage also involves a capacity to face others as moral agents, and thus in a manner that does not objectify them. A moral stand can only be taken toward another moral agent. Often, we find ourselves unable to face others in this way, because to do so is frightening, or because we are consumed by blinding anger. But without facing others as moral subjects, we risk moral cowardice on the one hand and moral fanaticism on the other.